Digital and social media marketing : a results-driven approach - Heinze, Aleksej; Fletcher, Gordon; Rashid, Tahir; Cruz, Ana (New York, NY : Routledge, 2020)
'The second edition of Digital and Social Media Marketing is an up to date, industry-led results-driven guide to digital marketing. Mixing academic theory with practical examples from a range of different organisations worldwide, it provides insight into, and techniques to enable, the creation, development and maintenance of a successful digital presence. This highly regarded textbook has been fully revised to bring the content up to date with the newest digital technologies. With topics including developing an effective digital presence, search engine optimization, and measuring brand awareness, the new edition also looks at digital ethics, General Data Protection Regulation (GDPR) and privacy, Artificial Intelligence (AI) and Machine Learning, and Voice strategies. New international case studies are explored, including Alibaba and Amazon, as well as revised practical exercises in each chapter, enable students to see how the concepts underpinning digital and social media marketing support business success. The book's customisable Digital Business Maturity Model, and the Buyer Persona Spring, offer organisations a clear roadmap for understanding their own levels of technology adoption and digital strategy development. This accessible textbook provides a hands-on, user-friendly platform to turn skills and knowledge into strategic advantage. It is ideal for advanced undergraduate and postgraduate students of digital marketing and marketing strategy, and for practitioners aiming to be at the cutting edge of Digital and Social Media Marketing. Alongside electronic resources for each chapter, this new edition also includes digital learning materials, case studies and exercises available in a supporting online learning environment. The online materials further enhance learners' experience and supports a worldwide learning community'--
Includes bibliographical references and index.
Keywords: Internet marketing; Internet advertising; Electronic commerce; Social media